Body fatness and endogenous sex hormones in the menopausal transition. (May 2016) - Zsakai, Annamaria; Karkus, Zsolt; Utczas, Katinka; Biri, Beata; Sievert, Lynnette L.; Bodzsar, Eva B.
Highlights: The literature regarding the relationship between sex hormonal levels and body fatness in relation to reproductive ageing was examined. In a sample of 1932 women, body fat mass in those who demonstrated low levels of sex hormones, but experienced regular menstruation, was always above the age-median value of the menopausal status subgroups. Body fat mass of women with high levels of sex hormone levels, who were amenorrheic at least for the past 12 months, was below the age-median values. Abstract: Background: Age at the final menstrual period is of clinical and public health interest because the age at which natural menopause occurs may be a marker of ageing and health, and in general the menopausal transition increases the risk of many diseases, e.g. redistribution in the pattern of adiposity during the menopausal transition may increase risk of metabolic disease. The purpose of this research was to study the relationship between the menopausal status and body fatness. Subjects and methods: A random sample of 1932Hungarian women was studied. Body composition was estimated by body impedance analysis. In a subsample free estradiol and progesterone levels in saliva were quantified. Results: Body fat mass increased until the late 50s and then had a decrease through senescence. Premenopausal women who were much older than the median age at menopause had a higher amount of fat than their postmenopausal age-peers, while postmenopausal women, whose menopause occurred much earlier than the median age at menopause, had less fat than their premenopausal age-peers. The body fat mass in premenopausal women with low levels of sex hormones was always below the age-median value of the menopausal status subgroups, while the body fat mass of postmenopausal women with high levels of sex hormone levels was above the age-median values. Conclusions: The analysis of body fatness in the menopausal transition revealed that (1) the rate of reproductive ageing and the body fat pattern were significantly related, and (2) body fat mass of women with unexpected levels of sex hormones was related more to their hormonal levels than to their menopausal status or their age. Thus future epidemiological screenings of women exposed to higher levels of menopause-related health risks should be expanded beyond the estimation of menopausal status based only on menstrual history to include sex hormone level assessment, as well as body composition analysis.